Fragilidade ambiental da Bacia do Arroio Guarda Mor - Dambroz, Alice Prates Bisso (2020)
Erosion hotspots act as sediment sources and are responsible for the transfer of sediments, nutrients and pollutants, leading to soil and water degradation. The erosive process occurs on variable and continuous range of scales and this variability is not addressed by a holistic approach or model. Complementary tools that integrate geomorphology, erosion modelling and sediment yield were used to identify such spots and to comprehend their fragilities. The study was carried on three environmentally fragile paired headwater sub catchments (S1, S2 and S3) nested in Guarda Mor catchment, located in a geomorphological transition between the Plateau and Central Depression of Rio Grande do Sul. Three work packs were analyzed. WP1 addresses zones of relief-influenced erosion, by primary and secondary topographic attributes. WP2 consists of a dynamic simulation of runoff, erosion and sediment yield with WATERSED model, adding to topography, climate, soil and land use factors. Last, WP3 identifies sediment sources by means of an alternative fingerprinting technique. Support vector machine prediction models were built based on soil and sediment samples’ near-infrared spectrum. Slope, Topographic Wetness Index, Stream Power Index and Slope Length and Steepness Factor (LS Factor) show a similar geomorphological arrangement for S1 and S3, indicating their slightly greater erosive susceptibility than S2. The hotspots seem to be located near the drainage network and steepest areas. The same was indicated by WP2, with increased evidence by higher magnitude rainfall events. The sub catchment S2 shows greater potential for runoff and sediment yield. Fingerprinting results greatest contribution from unpaved roads to S1 and S2 and from topsoil to S3. As for tracing tributaries, results indicate that nearly 90% of sediment at Guarda Mor’s outlet come from S1. The result may be due to unsampled sources in between source and sink. The combination of analyses provided different and complementary results. WP1 and WP2 show the areas adjacent to the drainage network for all sub catchments as the most fragile. Short distances from source to river promote good connectivity for material transfer. Similarities between S1 and S3 did not lead to similar sediment contributions. Fingerprinting added information regarding the importance of unpaved roads and erosion in the drainage network to erosion and sediment yield. This landscape component is not addressed by WP1 and WP2. Topsoil and stream channels are also significant sediment sources. Geomorphology can represent these areas’ susceptibility to erosion, more detailed maps may overcome the lack of representation of roads. Further analysis should consider unsampled sources between the sub catchments’ outlets and GMex.